2014
DOI: 10.1093/cercor/bhu131
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Facilitatory Mechanisms of Auditory Attention After Damage of the Lateral Prefrontal Cortex

Abstract: There is growing evidence that auditory selective attention operates via distinct facilitatory and inhibitory mechanisms enabling selective enhancement and suppression of sound processing, respectively. The lateral prefrontal cortex (LPFC) plays a crucial role in the top-down control of selective attention. However, whether the LPFC controls facilitatory, inhibitory, or both attentional mechanisms is unclear. Facilitatory and inhibitory mechanisms were assessed, in patients with LPFC damage, by comparing event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…These decreased extrastriate neural responses were accompanied by impairments in the ability to detect targets presented in the contralesional visual field. Diminished neural responses have been similarly reported in DLPFC patients during selective auditory attention (Bidet-Caulet et al, 2014). These studies suggest that the DLPFC plays an important role in attention by providing top-down facilitatory input to sensory cortices.…”
Section: Lesions To Dorsolateral Pfcmentioning
confidence: 61%
“…These decreased extrastriate neural responses were accompanied by impairments in the ability to detect targets presented in the contralesional visual field. Diminished neural responses have been similarly reported in DLPFC patients during selective auditory attention (Bidet-Caulet et al, 2014). These studies suggest that the DLPFC plays an important role in attention by providing top-down facilitatory input to sensory cortices.…”
Section: Lesions To Dorsolateral Pfcmentioning
confidence: 61%
“…However, it has also been shown to be involved in cognitive processes 18, 43, 62, 96 , such as attention 6, 104106 , value encoding 11, 40, 46, 53, 95 , working memory 5 , creativity 52 , decision-making 71, 73 , and emotional regulation 15, 27, 29, 67, 99 .…”
Section: Dlpfc Functionmentioning
confidence: 99%
“…Both prefrontal (Green, Doesburg et al 2011, Bidet-Caulet, Buchanan et al 2015 and parietal (Michalka, Rosen et al 2016, Deng, Reinhart et al 2019, Deng, Choi et al 2020) cortex have been shown to play important roles in auditory spatial attention in humans. Although we found clear responses related to the cued side in dlPFC, they followed AC.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial selective listening is critical for solving everyday problems including the "cocktail party problem", which requires attending to one sound source amidst a noisy background of competing sources (Cherry 1953). Common auditory spatial selective listening paradigms in research with humans include modified Posner paradigms in which subjects have to detect auditory stimuli after being cued to a spatial location (Spence and Driver 1994, Alho, Medvedev et al 1999, McDonald and Ward 1999, Mayer, Harrington et al 2007, Mayer, Mannell et al 2009, Roberts, Summerfield et al 2009, Teshiba, Ling et al 2013) and selective listening studies (Ahveninen, Huang et al 2013, Frey, Mainy et al 2014, Bidet-Caulet, Buchanan et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation